BURNOUT SYNDROME IN YOUNG FEMALE VOLLEYBALL ATHLETES PARTICIPANTS OF THE BRAZILIAN CHAMPIONSHIP TEAMS - Marcelo de Castro Teixeira; Marco Túlio Silva Batista; Leandro Rafael Leite; Sandro Fernandes Da Silva (Journal of Physical Education)
ABSTRACT Volleyball is one of the leading sports in Brazil and, in order to achieve good competitive levels, many training sessions are required which consequently generates physical and psychological wear. The result of this process can lead to chronic stress in practitioners, known as the Burnout Syndrome. This study aimed to investigate the occurrence of this syndrome in volleyball female athletes participating on the Brazilian Regional Teams Championship 2013. The Athlete burnout Questionnaire was answered by 576 players (M = 16.4years, SD = 1.12). We used descriptive statistics of mean and standard deviation to characterize the syndrome and the non-parametric correlation test of Kendall's tau-b to verify the correlation between the dimensions of burnout and the Practice Time (PT). The athletes presented mean scores (2.01±0:53) for complete burnout and significant correlations with TP of seven years or more in addition to the General.